Toward homogenization of Mediterranean lagoons and their loss of hydrodiversity. Issue 16 (19th August 2014) - Ferrarin, Christian; Bajo, Marco; Bellafiore, Debora; Cucco, Andrea; De Pascalis, Francesca; Ghezzo, Michol; Umgiesser, Georg
Abstract Lagoons are considered to be the most valuable systems of the Mediterranean coastal area, with crucial ecological, historical, economical, and social relevance. Climate change strongly affects coastal areas and can deeply change the status of transitional areas like lagoons. Herein we investigate the hydrological response of 10 Mediterranean lagoons to climate change by means of numerical models. Our results suggest that Mediterranean lagoons amplify the salinity and temperature changes expected for the open sea. Moreover, numerical simulations indicate that there will be a general loss of intralagoon and interlagoon variability of their physical properties. Therefore, as a result of climate change, we see on Mediterranean lagoons an example of a common process that in future may effect many coastal environments: that of homogenization of the physical characteristics with a tendency toward marinization.